Evaluation of insecticides and natural product for their efficacy against shoot borer (Conogethes punctiferalis Guen.) (Lepidoptera: Crambidae) infesting ginger (Zingiber officinale Rosc.) - S Devasahayam, C M Senthil Kumar*, T K Jacob, (Journal of Spices and Aromatic Crops, 2017)
Nine insecticides and a natural product were evaluated in the field at Peruvannamuzhi (Kerala) for their efficacy against shoot borer (Conogethes punctiferalis), a serious insect pest of ginger (Zingiber officinale) for two years. Pooled analysis of two years data indicated that chlorantraniliprole 0.01% was the best treatment with a mean pseudostem damage of 2.6% which was on par with flubendiamide 0.02% (4.1%), spinosad 0.0225% (6.5%) and cyantraniliprole 0.005% (8.8%), when sprayed at 15 day intervals during the second fortnight of July to the first fortnight of November. The trials indicated that that these low-risk insecticides and natural product can be utilized for the management of C. punctiferalis in ginger with reduced risk to the environment.